Tree shrew as a new animal model for the study of lung cancer - YE, LIANHUA (Oncol Lett, 2016)
Animal models play a key role in identifying treatments for various types of cancer, including lung cancer. The aim of the present study was to develop a new animal model for lung cancer induction using tree shrews from the Yunnan region in China. Tree shrews are suitable for a full simulation of human disease because their structure, function and metabolism are adequately close to human. This animal may offer a new experimental animal model to be used in the study of lung cancer. In the present study, 80 healthy tree shrews were distributed in experimental and control groups. Animals in the experimental group received different concentrations of iodized oil suspension of 3-methylcholanthrene (3-MC) and diethylnitrosamine (DEN) while animals in the control groups received saline or lipiodol solvent via endotracheal instillation. In the 3rd, 5th, 7th, 9th and 11th weeks the body weights of the animals were measured and chest X-ray examinations were conducted. Pathological studies on the lung tissues were also performed and the pathological changes occurring in bronchial epithelium in all the groups were examined. Animals in the experimental group gradually lost their body weight. For tree shrews in the blank control and solvent control groups the survival rates were 100 and 80%, respectively while the survival rate for the experimental group was 0%. Results from the chest X-ray conducted on animals in the blank control and solvent control groups revealed no obvious abnormalities while in the experimental group high-density shadow spots within the perfusion sites were observed. Pathological studies performed on these high-density areas confirmed changes in the bronchial epithelium. In the experimental groups we also detected bronchial epithelial atypical hyperplasia, and apparent changes in carcinoma in situ. In conclusion, lung cancer was successfully induced in tree shrews by a one-time endotracheal introduction of iodized oil suspension of 3-MC and DEN.